Investigation of electrochemical mechanisms of solid oxide fuel cells - Chen, Xiaojun. (2008)
The depletion of fossil fuel and environmental pollution has led to an urgent demand for alternative energy sources and efficient energy conversion methods. Solid oxide fuel cells (SOFCs), generally operating in the temperature range of 600 – 1000 C, have drawn attention for its high-energy utilization efficiency and negligible pollutant emissions.